The Legal Education Revolution that Failed – Attempts to Establish a Legal University in Victorian Britain - Andrew Watson (Journal on European History of Law, 2023)
Concern about the quality of legal education of solicitors and barristers in England led to the House of Commons Select Committee 1846, which recommended major reform, as did the Royal Commission of 1855: Both advocated a “College of Law” or “Legal University”, though not including solicitors’ articled clerks, who were to have their own “cognate” institution. Against this, the campaign in the 1870 s, initially well supported, to establish a comprehensive “General School of Law” or “University of Law”, which would have amounted to a revolution in legal education in England, is described. Reasons are advanced for its failure and the consequences of this outlined. Speculation follows what might have been if the General School of Law/ University of Law had been established.